2014
DOI: 10.1097/opx.0000000000000245
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Aniseikonia Inspector Version 3 in School-Aged Children

Abstract: Most children were able to complete aniseikonia testing with AI3. Background aniseikonia was clinically insignificant (0.59%), and induced aniseikonia measurements were close to expected values using a 4% size lens. Aniseikonia Inspector Version 3 appears to be a useful means for measuring aniseikonia in a normal pediatric population. Further study in children with anisometropia is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…This is the first study demonstrating that aniseikonia tests can be reliably performed in adults with anisometropic amblyopia. Previous studies have excluded participants who did not demonstrate simultaneous perception or stereopsis (Antona et al 2007;Awaya S 1982;Kehler et al 2014;Lubkin et al 1999) as aniseikonia was assumed to be difficult to measure in amblyopia due to suppression. While Lubkin et al (1999) investigated the relationships between aniseikonia, anisometropia, strabismus, and amblyopia, their participants had very low levels of suppression as they were required to have stereopsis of 100 secs of arc or better to perform Space Eikonometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study demonstrating that aniseikonia tests can be reliably performed in adults with anisometropic amblyopia. Previous studies have excluded participants who did not demonstrate simultaneous perception or stereopsis (Antona et al 2007;Awaya S 1982;Kehler et al 2014;Lubkin et al 1999) as aniseikonia was assumed to be difficult to measure in amblyopia due to suppression. While Lubkin et al (1999) investigated the relationships between aniseikonia, anisometropia, strabismus, and amblyopia, their participants had very low levels of suppression as they were required to have stereopsis of 100 secs of arc or better to perform Space Eikonometry.…”
Section: Discussionmentioning
confidence: 99%
“…Internationally there does not appear to be a 'gold standard' test used for the measurement of aniseikonia. The Aniseikonia Inspector version 3 (AI3) (Optical Diagnostics, Culemborg, The Netherlands) (Kehler et al 2014) and the New Aniseikonia Test (NAT) (Good-Lite Company, Tokyo, Japan) (McCormack et al 1992) are two of the more routinely used clinical tests, but there is a lack of evidence around test comparisons and reliability between tests. In this study we investigated the use of 4 different subjective aniseikonia tests on three groups of participants: those with anisometropic amblyopia, anisometropia and no amblyopia, and isometropic controls.…”
Section: Introductionmentioning
confidence: 99%
“…This computer‐based test requires patients to directly compare two rectangles viewed through red‐green anaglyphic glasses, thus simultaneous perception with minimal suppression is required. The forced‐choice method and the short testing time (approximately four minutes) makes this a simple and quick test to be performed in all age groups, including children aged as young as five years …”
Section: Testing For Aniseikoniamentioning
confidence: 99%
“…18 Finally, the only published study employing Version 3 has reported acceptably accurate measurements of lens-induced aniseikonia in the short presentation mode with central fixation. 20 Misestimation of aniseikonia has been claimed to be clinically irrelevant [21][22][23] because further checks can be conducted before or after prescribing iseikonic spectacle lenses, although the process is lengthy and may be expensive. Yet, identifying the cause of the underestimation in the NAT and the AI Version 1 as well as the cause of the conflicting patterns of misestimation across versions of the AI is a problem whose solution could render improved tests that save time and costs to patients in clinical practice, also helping to prevent analogous problems that might arise in the use of psychophysical methods for the assessment of other visual functions.…”
Section: Introductionmentioning
confidence: 99%